Model Integrasi Islam dan Sains di Perguruan Tinggi Keagamaan Islam: Integration Model of Islam and Science at Islamic University - Siti Mutholingah (STAI Ma'had Aly Al-Hikam Malang, 2024)
The purpose of this study is (1) to analyze how the concept of integration of Islam and science at PTKI (Islamic university) and (2) to analyze the model of the paradigm of science and integrative education at UIN Maulana Malik Ibrahim Malang. This study uses a library research type. The results of this study are: (1) The concept of integration of Islam with science (and technology) is an effort to develop one modern science in a particular field that is based on the foundation of divine awareness and the values ​​of Islamic teachings (belief, morals, worship, muamalah). (2) The integrative scientific paradigm at UIN Maulana Malik Ibrahim Malang is an integrative scientific paradigm between sciences sourced from the Qur’an and Hadith (verses of Qauliyyah) with sciences from the results of observation, experiments, and logical reasoning (verses of Kauniyyah). The integrative education model at UIN Maulana Malik Ibrahim Malang is the integration of higher education institutions (as a place for sowing science) with Ma’had Aly (as a place for sowing Islam) and the integration of Islamic and scientific knowledge in the form of courses in each faculty. Tujuan penelitian ini: (1) untuk menganalisis bagaimana konsep integrasi Islam dan sain di PTKI; (2) untuk menganalisis model paradigma keilmuan dan pendidikan integratif di UIN Maulana Malik Ibrahim Malang. Penelitian ini menggunakan jenis penelitian pustaka. Adapun hasil dari penelitian ini: (1) Konsep integrasi Islam dengan sains (dan teknologi) yaitu sebagai upaya dalam mengembangkan satu keilmuan sains modern di bidang tertentu yang dilandasi pondasi kesadaran ketuhanan dan nilai-nilai ajaran Islam (akidah, akhlak, ibadah, muamalah); (2) Paradigma keilmuan integratif yang ada di UIN Maulana Malik Ibrahim Malang merupakan paradigma keilmuan integratif antara ilmu-ilmu yang bersumber Al-Qur’an dan Hadis (Ayat-ayat Qauliyyah) dengan ilmu-ilmu dari hasil observasi, eksperimen, maupun penalaran logis (ayat-ayat Kauniyyah). Adapun model pendidikan integratif yang ada di UIN Maulana Malik Ibrahim Malang yaitu integrasi kelembagaan pendidikan tinggi (sebagai wadah penyemai sains) dengan Ma’had Aly (sebagai wadah penyemai Islam) dan integrasi keilmuan Islam dan sains yang berbentuk matakuliah di masing-masing fakultas. Kata Kunci: Integrasi, Islam, Sains, Pendidikan Integratif.